(untitled) (Czech Journal of International Relations, 2002)
Jonathan Krueger: International Trade and the Basel Convention. Trade and Environment Series. 1st ed. London: The Royal Institute of International Affairs/Earthscan, 1999, 133 s., ISBN 1853836214.